The relationship between diet and weight training with ideal body shape among members of Katamso Fitness Centre, Medan City - Sebayang, Robby Gunawan; Polem, Fahmi; Siregar, Hesti Despita; Putri, Lenni Dianna; Kunardi, Sidharta; Fransisca, Silvia; Bestari, Welas; Tarigan, Antje Irmella; Janice, Janice; Arhamni, Ade; Kurniawan, Evan (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Katamso Fitness Centre is a gym surrounded by individuals aiming for an ideal and healthy physique. Members typically join to address less-than-ideal body weight and seek weight training to achieve their desired body shape—transforming from thin to muscular, or from overweight to lean, while also burning calories for overall health and fitness. This study employed a Chi-Square statistical test using SPSS for Windows, with a significance level of α=0.05. This analysis aimed to examine the relationship between independent and dependent variables. The research findings from 86 respondents indicate that the majority, 57 (66.3%), had a more ideal body shape. For diet patterns, the majority, 66 (76.7%), reported